The effect of airline passenger anthropometry on aircraft emergency evacuations. (August 2020) - Melis, Damien J.; Silva, Jose M.; Yeun, Richard; Wild, Graham
Highlights: Current aircraft evacuation certification rules do not reflect demographic trends. An increasing obesity prevalence will increase aircraft evacuation times. When a population of increased BMI is assumed the egress time exceeds 90 s. An anthropometric characteristics model is created for emergency egress simulations. Abstract: This paper demonstrates the impact of passenger anthropometry on the emergency egress for both single aisle and double aisle aircraft. A demographic model of passenger anthropometry based on Body Mass Index (BMI) categories was developed building upon data retrieved from an online database. Knowing that the prevalence of obesity is becoming greater at a global scale, various obesity condition were simulated to explore the effects of an increased number of obese/overweight passenger on-board medium and large aircrafts. Verification of the software used in egress simulations was carried out by undertaking a trial mimicking a real-life evacuation. The simulated results show that for current levels of BMI prevalence the time to evacuate an aircraft is 76.6 s (95% CI, 76.2–76.9) for a narrow-body and 87.1 s (95% CI, 86.7–87.7) for a wide-body aircraft. Leaving current prevalence of BMI categories unchanged but increasing overall obesity by just 5% can lead to an increase of the egress time of approximately 2 s for the wide-body aircraft scenario. The egress time is significantly increased when greater percentages of obese passengers are considered. The results show that the egress time for a population with a demographic distribution similar to that expected in the next 30 years exceeds the current time limit of 90 s considered by aviation authorities for certification purposes of passenger aircraft.